Swedish folk high school database - Nylander, Erik (Linköping University, 2022)
The Swedish folk high school database collects the catalogs of folk high schools between the years 1952-2019. The catalogs contain descriptions of the folk high school as a form of education as well as details of the courses offered by the schools. It is possible to search for subjects, words or phrases and also download the catalogs. The database is a valuable resource for, among others, researchers, folk high school teachers and principals.

Folkhögskoledatabasen samlar folkhögskolornas nationella kurskataloger mellan åren 1952-2019. Katalogerna innehåller beskrivningar av folkhögskolan som utbildningsform samt specifikationer över det kursutbud skolorna tillhandahållit. Det är möjligt att söka efter ämnen, ord eller fraser samt ladda ned katalogerna. Databasen är en värdefull resurs för bland annat forskare, folkhögskollärare och rektorer.
Folkhögskoledatabasen
Keywords: ADULT EDUCATION INSTITUTIONS; VUXENUTBILDNINGSINSTITUTIONER; Folk high school; Folkhögskola; EDUCATION; UTBILDNING; Educational Sciences; Utbildningsvetenskap